Identifikasi Kualitatif Senyawa Terpenoid Ekstrak N- Heksana Sediaan Losion Daun Jeruk Purut (Citrus Hystrix Dc) - Yuniar Indo Masadi; Titik Lestari; Indri Kusuma Dewi (Jurnal Kebidanan dan Kesehatan Tradisional, 2018)
Abstrack : Physical Characteristic, Qualitative Terpenoid Experiment, Lotion, Lime Leaves. Lime leaves (Citrus hystrix DC.) contain active tannin compounds, steroid, terpenoid, and volatile oil which be formulated into repellent lotion. The aim of this research was to find out the physical testdosage form extract lotion of lime leaves covering organoleptic, homogeneity, pH, viscosity, dispersive power and adhesion, and also qualitative testing to find out the compounds content of terpenoid dosage form extract lotion of lime leaves. Methodology of this research used descriptive observational study by observes then describe about physical characteristic. The result of qualitative test terpenoid compound form extract lotion of lime leaves presented in narration and table. The result of this research was organoleptic experiment that showed if dosage form extract lotion of lime leaves have viscous and semi-solid, green color, fragrant smell typical of lime leaves. Homogeneity form was less homogeneous because there is still a little green particle. pHdosage form got the result for 6,27. Viscosity dosage form got the result for 4500 cp (centipoise). Dispersive power dosage form got the result for 6,6 cm. Adhesion got the result for 1,28 second and the result of qualitative experiment showed positive result and contains terpenoid with sorrel color. The conclusion from this research was the result from physical experiment dosage form extract lotion of lime leaves got appropriate with standard except homogeneity experiment and qualitative experiment of terpenoid compounds got the positive result contains terpenoid.